ROHINGYA REFUGEES IN INDONESIA: THE DYNAMICS OF STATELESSNESS AND THE VIEWS OF LOCAL PEOPLE - Irwansyah Irwansyah; Al'asyari Al'asyari; Rholand Muary (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
Rohingya refugees who are experiencing a crisis due to the genocide in Myanmar have attracted international attention. The existence of the Rohinghya as an ethno-religious minority group was officially discriminated against which led to forced expulsion by the Myanmar government in 1982 with the issuance of the citizenship law which stated that Rohingya citizenship was denied or not recognized as one of the official ethnicities in Myanmar. So, the Rohingya were forced to flee their country to other countries, including Indonesia. This paper aims to determine the dynamics of Rohingya Muslims while in Indonesia. Using qualitative research methods by conducting observations, interviews and data analysis. The results of this study indicate that the Rohingya ethnicity in Indonesia as stateless (without citizenship) undergoes a process of acculturation, marriage with local Indonesian citizens (WNI), and developing survival strategies because some have lived in Indonesia for more than eight years. In conclusion, the Rohingya ethnicity while in Indonesia experienced conditions of uncertainty in their lives because they did not have citizenship status and hoped to be sent to a third country by UNHCR. Indonesian people accept Rohingya Muslims to stay in Indonesia temporarily because there is a common Islamic identity and in the name of humanity.